La tradizione dei Profeti nei codici in beneventana: aspetti testuali e paratestuali - Casavecchia, Roberta (Scrineum, 2026)
The paper examines the paratextual apparatus of the biblical production in Beneventan script, specifically regarding the books of the Prophets, which in this graphic area were handed down as an autonomous collection, in accordance with the predominantly liturgical use of the Bible. The characteristic features revealed through the analysis of prologues, tabulae capitulorum and headings (tituli) emphasize the originality of the ‘Cassinese group’, even when compared to Beneventan Bibles produced outside of Montecassino, and contribute to a better understanding of certain aspects in the production and transmission of biblical manuscripts in Southern Italy.